How Electronic Word-of-Mouth Shapes Cross-Buying Intention through Brand Trust and Brand Image - Nguyen Khac, Nghia (Institut Agama Islam Negeri (IAIN) Curup, 2026)
This study investigates the impact of electronic word-of-mouth (eWOM) on cross-buying intention in the context of commercial banks in Vietnam. Specifically, it examines the mediating roles of brand trust and brand image in this relationship. A quantitative approach was employed using survey data collected from 409 respondents. The dataset was analyzed with SPSS 26 and AMOS 24 to validate the research model and test the proposed hypotheses. The findings reveal that eWOM significantly influences customers’ cross-buying intention, both directly and indirectly, through brand trust and brand image. These results highlight the importance of enhancing brand-related factors to leverage eWOM in fostering cross-buying behaviors. Based on these insights, the study provides managerial implications for commercial banks in developing effective strategies to strengthen customer relationships and promote service diversification.